Dampak Tsunami Terhadap Kesehatan Mental Anak - Bs. Titi Haerana; Alifka Rahmayanti Jamaluddin; Rimawati Aulia Insani Sadarang; Irwandi Rachman; Reski Ihsan Humang (FORIKES, 2022)
Indonesia's geographical, geological, hydrological and demographic conditions make this country prone to natural disasters. One of them is the tsunami disaster which can have an impact on the mental health of children psychologically, this impact is rarely a concern. The impact will cause long-term effects if you don't get the appropriate help. This study aims to assess the impact of the tsunami on children's mental health. The research method used was narrative review which was conducted by searching for published articles related to the impact of the tsunami on mental health. A literature search was conducted from 14 to 30 April 2021 through the Google Scholar database with the search keywords